The Effect of Learning Environment on Students' Motivation in Learning - Firman, Edi; S, K. Dedy Sandiarsa (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study investigates the relationship between the learning environment and students' motivation through qualitative analysis of interviews and focus groups. Key themes emerged highlighting the influence of various environmental aspects on motivation. Participants emphasized the importance of supportive teacher relationships, noting that teachers who demonstrate genuine interest and provide constructive feedback foster higher motivation levels. A positive classroom climate characterized by respect, collaboration, and inclusivity was also identified as crucial for engagement. Peer interactions, particularly through collaborative learning experiences, enhanced motivation by creating a sense of belonging and accountability. Additionally, access to diverse resources and learning tools was vital for maintaining motivation, with students expressing a desire for engaging materials. The physical characteristics of learning spaces, such as seating arrangements and lighting, significantly impacted motivation, with flexible and organized environments contributing to comfort and engagement. While many students appreciated technology's role in facilitating interactive learning, concerns about distractions underscored the need for balanced integration. Overall, the findings align with existing literature, offering new insights into factors influencing motivation across educational levels. The study underscores the necessity for educators to foster supportive relationships, promote a positive classroom climate, provide diverse resources, and thoughtfully integrate technology, ultimately enhancing student engagement and success. Future research should further explore these dynamics, particularly in the context of evolving educational practices and technological advancements.